Respiratory failure with diffuse patchy lung infiltrates: an unusual presentation of squamous cell carcinoma. Issue 12 (December 1994) - Meysman, Marc; Schoors, Danny F; Reynaert, Hendrik; Noppen, Marc; Pierre, Erwin; Vincken, Walter
Abstract : The case history is presented of a patient with squamous cell carcinoma of the lung with diffuse bilateral pulmonary shadowing mimicking bronchioloalveolar cell carcinoma which led to type I respiratory failure.